Gradual sucrose gastric loading test: A method for the prediction of nonsuccess gastric enteral feeding in critically ill surgical patients - Chittawatanarat,K. (Medknow Publications and Media Pvt. Ltd, 2015)
Background and Aims: Intolerance of gastric enteral feeding (GEN) commonly occurs in surgical Intensive Care Unit (SICU). A liquid containing sugar could prolong gastric emptying time. This study was to propose a method for prediction of nonsuccess GEN using gastric volume after loading (GVAL) following gradual sucrose gastric loading. Materials and Methods: Mechanical ventilator supported and hemodynamically stable patients in SICU were enrolled. About 180-240 min before the GEN starting, a sucrose solution (12.5%; 450 mosmole/kg, 800 mL) was administered via gastric feeding tube over 30 min with 45° head upright position. GVAL was measured at 30, 60, 90, and 120 min after loading. GEN success status using clinical criteria was assessed at 72 h after the starting GEN protocol. The receiving operating characteristic (ROC) and c statistic were used for discrimination at each time point of GVAL. Results: A total of 32 patients were enrolled and completed the protocol. 14 patients (43.7%) were nonsuccessful GEN. The nonsuccess group was found to have significantly more GVAL than the other group at all-time points during the test (P < 0.05). The most discriminating point of GVAL for the prediction of nonsuccess was 150 mL at 120 min after loading with a sensitivity of 92.3%, specificity of 88.9%, positive predictive value of 85.7%, negative predictive value of 94.1%, and ROC area 0.97 (95% confidence interval 0.91-1.00). Conclusion: A high GVAL following sucrose gastric loading test might be a method to predict nonsuccess GEN in critically ill surgical patients.